2005
DOI: 10.1021/jf050761r
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Spray-Dried Tuna Oil Emulsions Encapsulated with Two-Layered Interfacial Membranes

Abstract: omega-3 Fatty acids have numerous health benefits, but their addition to foods is limited by oxidative rancidity. Spray-drying tuna oil-in-water emulsion droplets with a coating of lecithin and chitosan multilayer system could produce emulsion droplet interfacial membranes that are cationic and thick, both factors that can help control lipid oxidation. Physicochemical and oxidative stability of the spray-dried emulsions were determined as a function of storage temperature and relative humidity (RH). The combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 45 publications
9
90
0
3
Order By: Relevance
“…In the presented study, we also demonstrated no influence of surface oil content on the stability of encapsulated pumpkin seed oil. It is in agreement with the work of Klinkersorn et al (2005) who studied stability of spray-dried tuna oils.…”
Section: Oxidative Stability Of Encapsulated Pumpkin Seed Oilsupporting
confidence: 92%
“…In the presented study, we also demonstrated no influence of surface oil content on the stability of encapsulated pumpkin seed oil. It is in agreement with the work of Klinkersorn et al (2005) who studied stability of spray-dried tuna oils.…”
Section: Oxidative Stability Of Encapsulated Pumpkin Seed Oilsupporting
confidence: 92%
“…The process of oil microencapsulation consists basically in the preparation of an oil-in-water emulsion containing the matrix components in the aqueous phase, which is then dried [9]. Microencapsulation by spray drying has been found effective for retarding or suppressing the oxidation of unsaturated fatty acids [8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This work is related to our earlier studies of the influence of a cationic polysaccharide (chitosan) on the pH stability of emulsions containing lipid droplets coated by anionic surfactants (SDS or lecithin). [29][30][31][32][33][34][35][36][37] Nevertheless, the electrical charge on protein-coated droplets can be changed from positive (pH<pI) to negative (pH>pI) by adjusting the pH, whereas the charge on anionic surfactant-coated droplets remains highly negative across a wide pH range. Consequently, surfactant-coated and protein-coated droplets behave quite differently to pH when chitosan is present.…”
Section: Introductionmentioning
confidence: 99%